Knowledge mapping and visualization as a common ground between librarianship and scholarly communication: Qualitative and quantitative methods for improving semantic categorization and retrieval - Gregori, Liliana; Losito, Luca; Sirito, Paolo (Qualitative and Quantitative Methods in Libraries, 2017)
Current trends in the field of knowledge organization (KO) and a growing need for promoting scholarly communication are facing LIS professionals with new challenges as well as exciting opportunities. Also academic libraries are urged to reshape their workflows and to focus on  innovative technologies, in order to develop value-added services to its users: scholars, researchers and students. According to such scenario, the Central Library of Università Cattolica del Sacro Cuore in Milan, launched in early 2012 a multi-year project, aimed to improve qualitative and quantitative aspects of semantic categorization and retrieval.   A ross domain ontology, based upon the Protégé framework, is currently being developed. When released, the system will provide patrons and staff with a visual interface, common to the three different tools currently used to manage bibliographic information: The library automation system (notably the cataloguing module), the Online Public Access Catalogue, the institutional repository, named PubliCatt The main expected benefits are: rationalizing and optimizing the cataloguing process, facilitating and broadening access to all library resources, making institutional research products more visible and citable The paper will provide details about the project framework, as well as other notable deliverables, in particular: templates, best practices, lesson learned